Genetically elevated high‐density lipoprotein cholesterol through the cholesteryl ester transfer protein gene does not associate with risk of Alzheimer's disease. Issue 1 (21st September 2018) - Peloso, Gina M.; van der Lee, Sven J.; ,; Sims, R.; van der Lee, S.J.; Naj, A.C.; Bellenguez, C.; Badarinarayan, N.; Jakobsdottir, J.; Kunkle, B.W.; Boland, A.; Raybould, R.; et al.
Abstract: Introduction: There is conflicting evidence whether high‐density lipoprotein cholesterol (HDL‐C) is a risk factor for Alzheimer's disease (AD) and dementia. Genetic variation in the cholesteryl ester transfer protein ( CETP ) locus is associated with altered HDL‐C. We aimed to assess AD risk by genetically predicted HDL‐C. Methods: Ten single nucleotide polymorphisms within the CETP locus predicting HDL‐C were applied to the International Genomics of Alzheimer's Project (IGAP) exome chip stage 1 results in up 16, 097 late onset AD cases and 18, 077 cognitively normal elderly controls. We performed instrumental variables analysis using inverse variance weighting, weighted median, and MR‐Egger. Results: Based on 10 single nucleotide polymorphisms distinctly predicting HDL‐C in the CETP locus, we found that HDL‐C was not associated with risk of AD ( P  > .7). Discussion: Our study does not support the role of HDL‐C on risk of AD through HDL‐C altered by CETP . This study does not rule out other mechanisms by which HDL‐C affects risk of AD. Highlights: CETP SNPs were not associated with AD in a large sample of AD cases/controls. Genetically predicted HDL‐C through CETP does not associate with AD.